Frequency of Intensive Statin Therapy in Patients With Acute Coronary Syndrome Admitted to a Tertiary Care Center - Shiu, J.; Pearson, G.; Charrois, Theresa; Gyenes, G.; Koshman, S. (Elsevier Inc, 2012)
Intensive statin therapy (IST) has been shown to decrease cardiovascular events in patients with acute coronary syndrome (ACS). Numerous studies have described statin use for secondary prevention; however, few data have highlighted IST use after ACS. The objective of the present study was to describe IST use in an ACS population before hospitalization, on discharge, and during early follow-up after discharge. A retrospective chart review was conducted of randomly selected patients admitted to a tertiary care center from November 1, 2007 to October 31, 2008. Eligible patients included adults admitted to cardiology with a most responsible diagnosis of ACS (International Classification of Diseases code 20-25). The exclusion criteria included transfer to another hospital or cardiovascular surgery ward and in-hospital death. Phase 1 included an inpatient chart review. Phase 2 was a follow-up cardiologist clinic letter review that included only patients who started IST in-hospital. Of 234 charts reviewed, 111 (47%) patients met the inclusion criteria (mean age 65 plus/minus 11.7 years, 76% men). Most patients (93%) were discharged with a statin. However, although 72% of the study population were eligible for IST, only 52% had IST during hospitalization. Of the patients who started IST with clinic letters available (n = 31), 68% continued IST (mean interval to follow-up 85 days, range 33 to 208). In conclusion, although statin use is good, IST use after ACS is suboptimal.